'We have to be a little more realistic': women's outdoor recreation experiences in a community hiking group. Issue 3 (27th May 2022) - McAnirlin, Olivia; Maddox, Callie Batts
ABSTRACT: Grounded in the theoretical framework of ecological feminism, this study explores the tension between constraint and empowerment that often marks women's participation in outdoor recreation. Drawing on ethnographic fieldwork and thirteen semi-structured interviews, this study examines how women in a co-ed community hiking group in the Midwest region of the United States experience the gendered space of outdoor recreation. Analysis of the observational and interview data resulted in five themes: Empowerment, Being Healthy, Cultural Expectations of Age, Vulnerability, and Navigation. Focusing on the latter three, we suggest that women's experiences are impacted by gendered assumptions (such as a lack of navigational skill) and socialized beliefs (such as the fear of being alone) that temper the potential for expected outcomes of personal empowerment and improved physical and mental health.